A SMART-BASED DECISION-MAKING FRAMEWORK FOR PRIORITIZING ENERGY EFFICIENCY INITIATIVES: A CASE STUDY OF AN INDONESIAN RETAIL COMPANY - Farah Nadira Iriawan; Pri Hermawan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study develops a SMART-based decision-making framework to prioritize Energy Efficiency initiatives in an Indonesian retail company. PT Prima Retail Lestari (PT PRL) is a retailer which faces budget and operational constraints, while several Energy Efficiency initiatives are available and have different financial, ESG, feasibility, and risk implications. An applied case study method will be used. The data will be gathered through semi-structured interviews, questionnaires, and document analysis. Situational Appraisal and Kepner-Tregoe Problem Analysis will be used to clarify the decision making gap, while the SMART method will be used to compare five initiatives: Refrigerant Transition, Rooftop Solar Panel Implementation, LED Lighting Transition, Water Loop Refrigeration System, and HVAC Efficiency Improvement. The result shows that ESG contribution and financial impact are the most important criteria with normalized weights of 0.30 and 0.28, respectively. Rooftop Solar Panel Implementation gets the highest weighted score of 4.00, followed by LED Lighting Transition with 3.92 and Water Loop Refrigeration System with 3.86. The study recommends prioritizing rooftop solar, implementing LED transition in parallel, and preparing water loop refrigeration as a long term initiative.